Peningkatan Kompetensi Pendidik dalam Perencanaan dan Administrasi Akademik PAUD - Tri Mulat; Hanipudin, Sarno (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Background of the community service arises from the condition of most early childhood education institutions (PAUD) in Bantul District, which still face obstacles in lesson planning, academic administration, and continuous evaluation. In fact, proper academic governance is crucial to ensure the quality of early childhood education as the foundation for character, knowledge, and skills development. The approach used is Community-Based Research (CBR), while the community service method is implemented through mentoring, training, workshops, and monitoring for educators and administrators. Activities focus on developing the KOSP (School Operational Plan), semester programs, learning tools, academic administration, and the use of simple technology in management. The method of implementation was carried out through mentoring, training, workshops, and monitoring for teachers and administrators. The activities focused on the preparation of KOSP, semester programs, learning tools, academic administration, and the utilization of simple technology for management support.